Contrasts in living conditions - Peter van Noorden (Cambridge Univ, 1990)
The book focuses on the regional differences between living conditions: the contrasts in access to basic needs such as food, shelter, work and recreation. These differences are studied on global, regional and local scales, both comparatively and longitudinally. It includes full colour aerial photographs, satellite images and topographic maps